Classification of Family Rights and Obligations: Doctrinal Foundations and Integration with the Principles of Sustainable Development - Vatras, Volodymyr; Oksaniuk, Oleg; Sydorenko, Denys; Sabluk, Serhii; Yakymchuk, Svitlana (European Journal of Sustainable Development, 2025)
This topic is important since family laws need to change with societal modernization, especially to ensure equal rights and responsibilities for spouses, improve parents' duties to inform children and make child support collection more effective. The research aims to analyze family law issues, discover current trends, and suggest possible solutions through analysis of laws, legal rulings, and scholarly articles using methods of comparison, analysis, and historical research. The research shows that unequal rights and responsibilities between spouses remain a serious problem, parents' responsibility to provide children with information should be clearly written in the law, and mechanisms for collecting alimony should be strengthened. The practical significance lies in proposals for improving legislation in the field of family law: which will help protect the rights of all participants in family relations by taking into account international experience and harmonizing national laws with international standards. Keywords: family law, alimony, parental rights, international standards, artups, innovations, technological development, venture financing, entrepreneurship, principles of sustainable development.